Development of Sn-Cu filled activated carbon composite solder via powder metallurgy technique
The revolution of electronic applications which have been assembled in smaller parts, lighter and more functional, causes the solder to become crucial over the worlds. These classes of low melting point alloys must provide a unique set properties to ensure the reliability of the electronic assemblies also allowing the joints to become more functional. A composite Sn-0.7Cu based solder was successfully fabricated via powder metallurgy (PM) technique which consist of mixing, compacting and sintering processes. Varying amount of activated carbon (AC); 0, 0.05, 0.1, 0.15 and 0.2 wt% were used as reinforcement to obtain a new lead-free composite solder. The parameters of PM technique which are mixing time, compacting loads and sintering time were varied and these parameters were optimized prior to composite solder synthesis. Subsequently, the lead-free composite solder were then subjected to physical mechanical and electrical tests. In this study, the best mixing time, compacting load and sintering time selected were 1h, 390 MPa and 141 s, respectively. Microstructure of the bulk solder after reflow process exposed significant improvements through addition of a small amount of AC particles into Sn-0.7Cu which had refined the microstructure of Sn-0.7Cu composite solder. The various percentages of AC particles were uniformly distributed along the β-Sn grain boundaries. The results revealed that melting temperature was slightly decreased with increasing the addition of AC particles; however still in acceptable range. The addition of AC particles slightly increased the electrical resistivity of Sn-0.7Cu solder. The wettability of the composite solder was improved where the best contact angle was 24.6⁰ for 0.2 wt% of AC particles. Meanwhile, the mechanical properties in terms of microhardness and shear strength experienced enhancements with addition of AC particles reinforcement where the 0.1 wt% of AC particles shows the best results among other percentages which was 12.14 Hv and 13.19 MPa, respectively. Furthermore, the roughness of the fracture surface increased with the increasing number of amounts of AC particles up to 0.15 wt%. The thickness of Cu6Sn5 IMC layer at the interface of the solder joint decreased to 2.16 μm with the addition of 0.1 wt% of AC particles. Overall, the addition of AC particles as reinforcement into Sn-0.7Cu lead-free solder based exhibit the enhancement of physical and mechanical properties compared with the solder matrix.